Pola Kemitraan PT. Ciomas Adisatwa Unit Bangkinang dalam Kerjasama Usaha Ternak Ayam Broiler Ditinjau dari Perpekstif Ekonomi Islam (Studi pada Usaha Ternak Ayam Broiler PT. Ciomas Adisatwa Unit Bangkinang) - Novita Sari (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2020)
The phenomenon of high public interest in business with Sharia-based Poultry Agribusiness Partnership, in which there is a proportional distribution of profits and losses. One company that applies a partnership pattern is PT. Ciomas Adisatwa Bangkinang unit. Nevertheless, a partnership system of PT. Ciomas Adisatwa Bangkinang unit is unknown whether it is based on the concept of Islamic economics or not. To reveal this, a qualitative approach was used in which the research informants were the head of PT Ciomas Adisatwa Bangkinang unit, the head of operations, the head of divisions, and an expert in Islamic Economics with snowball sampling technique. The results showed the partnership pattern implemented by PT Ciomas Adisatwa Bangkinang Unit was a plasma core partnership. This partnership pattern was analyzed based on the perspective of Islamic economics. As result, some processes were appropriate with the true concept of Syirkah and others were not.